A comparison of IROC and ACDS on‐site audits of reference and non‐reference dosimetry. Issue 12 (25th October 2019) - Lye, Jessica; Kry, Stephen; Shaw, Maddison; Gibbons, Francis; Keehan, Stephanie; Lehmann, Joerg; Kron, Tomas; Followill, David; Williams, Ivan
Abstract : Purpose: Consistency between different international quality assurance groups is important in the progress toward similar standards and expectations in radiotherapy dosimetry around the world, and in the context of consistent clinical trial data from international trial participants. This study compares the dosimetry audit methodology and results of two international quality assurance groups performing a side‐by‐side comparison at the same radiotherapy department, and interrogates the ability of the audits to detect deliberately introduced errors. Methods: A comparison of the core dosimetry components of reference and non‐reference audits was conducted by the Imaging and Radiation Oncology Core (IROC, Houston, USA) and the Australian Clinical Dosimetry Service (ACDS, Melbourne, Australia). A set of measurements were conducted over 2 days at an Australian radiation therapy facility in Melbourne. Each group evaluated the reference dosimetry, output factors, small field output factors, percentage depth dose (PDD), wedge, and off‐axis factors according to their standard protocols. IROC additionally investigated the Electron PDD and the ACDS investigated the effect of heterogeneities. In order to evaluate and compare the performance of these audits under suboptimal conditions, artificial errors in percentage depth dose (PDD), EDW, and small field output factors were introduced into the 6 MV beam model to simulate potential commissioning/modeling errors and both audits were tested for their sensitivity in detecting these errors. Results: With the plans from the clinical beam model, almost all results were within tolerance and at an optimal pass level. Good consistency was found between the two audits as almost all findings were consistent between them. Only two results were different between the results of IROC and the ACDS. The measurements of reference FFF photons showed a discrepancy of 0.7% between ACDS and IROC due to the inclusion of a 0.5% nonuniformity correction by the ACDS. The second difference between IROC and the ACDS was seen with the lung phantom. The asymmetric field behind lung measured by the ACDS was slightly (0.3%) above the ACDS's pass (optimal) level of 3.3%. IROC did not detect this issue because their measurements were all assessed in a homogeneous phantom. When errors were deliberately introduced neither audit was sensitive enough to pick up a 2% change to the small field output factors. The introduced PDD change was flagged by both audits. Similarly, the introduced error of using 25° wedge instead of 30° wedge was detectible in both audits as out of tolerance. Conclusions: Despite different equipment, approach, and scope of measurements in on‐site audits, there were clear similarities between the results from the two groups. This finding is encouraging in the context of a global harmonized approach to radiotherapy quality assurance and dosimetry audit.